1997
DOI: 10.1177/106002809703100101
|View full text |Cite
|
Sign up to set email alerts
|

Cost Comparison of Recombinant Human Erythropoietin and Blood Transfusion in Cancer Chemotherapy-Induced Anemia

Abstract: From a healthcare system cost and outcome perspective, blood transfusion is the preferred strategy for chemotherapy-induced anemia. However, rHuEPO may be considered an effective blood-sparing alternative for patients with non-stem cell disorders. Future cost-effectiveness analyses are needed to assess more completely both the clinical and quality-of-life benefits rHuEPO may contribute to individual patients' lives and to society overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
1
30
0
2
Order By: Relevance
“…In a cost comparison of rHuEPO vs leucocyte-depleted RBC transfusion therapy, with a response rate of 64% with rHuEPO, full cost of the drug and 8 months of therapy, RBC transfusion resulted in a saving of $8490 per patient (Sheffield et al, 1997). In a cost-effectiveness analysis that considered a longer duration for therapy and efficacy data from clinical trials (Barosi and Liberato, 1995), the baseline cost-effectiveness ratio was more than $100 000 per QALY.…”
Section: Resultsmentioning
confidence: 99%
“…In a cost comparison of rHuEPO vs leucocyte-depleted RBC transfusion therapy, with a response rate of 64% with rHuEPO, full cost of the drug and 8 months of therapy, RBC transfusion resulted in a saving of $8490 per patient (Sheffield et al, 1997). In a cost-effectiveness analysis that considered a longer duration for therapy and efficacy data from clinical trials (Barosi and Liberato, 1995), the baseline cost-effectiveness ratio was more than $100 000 per QALY.…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining the cost-effectiveness of epoetin used in the cancer setting have produced mixed conclusions, but these findings are based on clinical trial results from the early-tomid 1990s (Cremieux et al, 1999;Sheffield et al, 1997). Findings from more recently published clinical studies, including this one, suggest a need to examine the cost-effectiveness of epoetin b taking into consideration (1) the value of targeting patients using serologic markers at baseline and early in treatment, (2) the public concern about the safety of the blood supply and (3) the prospect that better anaemia management may improve survival.…”
Section: P<0001mentioning
confidence: 99%
“…Full texts were retrieved for 44 citations (the remainder being excluded as irrelevant on the basis of title and/or abstract). Five studies [114][115][116][117][118] were included following full-text screening (the remainder generally being excluded for not considering both costs and benefits). Figure 24 provides the study flow diagram for the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The incremental costs outweighed the benefits in monetary terms and the conclusion was therefore that epoetin alfa was less cost-effective than standard care with RBCT. Sheffield and colleagues 118 used a decision tree to model the costs and consequences of epoetin alfa use and concluded that epoetin alfa would be dominated by standard care with RBCT; that is, it would be more expensive and produce worse outcomes. Wilson and colleagues 2 highlighted several assumptions made that seemed implausible.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%